Solid waste at micro-drainage network - a qualitative analysis in the city of Pelotas/RS - Daltoé, Maurício Francisco (2016)
The Basic Sanitation at Brazil, according to the law nº 11.445/2007, includes about four aspects, the Supply of Potable Water, the Collection and the Treatment of Sewage, the Urban Cleaning and the Solid Waste Management, the Drainage and the Rainwater Management. The urban drainage and the solid waste management are of extreme relevance to the factors related to the present work, which aims to characterize so qualitative the solid waste found in micro-drainage network in the City of Pelotas – RS. The research was made at the period from August to October 2014 proposed to identify the main solid waste by means of photographic analysis checked in 11 different points at the micro-drainage network. The analysis made in micro-drainage network characterized a frequency of 100% of Plastic type 1, Wood and Organic Matter and the solid waste of least incidence were Rubber (27,27%) and Chemical Contaminants (9,09%).